Low threshold Rhodamine-doped whispering gallery mode microlasers fabricated by direct laser writing - Nathália B. Tomazio (Nature Portfolio, 2017)
Abstract The combination of the outstanding properties of whispering gallery modes with both the flexibility and ease of processing of polymers is particularly attractive for photonics applications. However, the versatile fabrication of polymeric nano/microdevices with the desired photonic performance has proven challenging. Here, we report on lasing in Rhodamine B doped whispering gallery mode microcavities fabricated by direct laser writing via two-photon polymerization. Threshold pump energies as low as 12 nJ were achieved for free-space pulsed excitation at 532 nm. To the best of our knowledge, this is the lowest laser threshold attained for microcavities fabricated in a single step of femtosecond laser writing, a remarkable feat that stands out from other fabrication methods.